Examining entry and exit rates of poverty in Turkey: A dynamic probit regression analysis - Bilik, Mustafa (Universitas Islam Indonesia, 2023)
Purpose: The purpose of this study is to add to the current poverty dynamics literature by investigating the underlying causes of poverty persistence in Turkey, with an emphasis on both entry and exit rates. Methods: The study analyzes data from the Turkish Statistical Institute's